What’s in a Name? Possible Ways Forward in the Macedonian Name Dispute - Kristijan Fidanovski (Slovo, 2018)
To download this article, click here. This paper provides an overview of the complex, 26-year-long name dispute between Macedonia/FYROM and Greece. It argues that the name talks have always been asymmetrical, with Greece dictating the terms due to its leverage over the Euro-Atlantic integration of Macedonia/FYROM. It also argues that this asymmetrical nature of the talks can be and has been mitigated by international pressure on Athens to compromise. The paper presents a strong correlation between constructive behaviour by Macedonia/FYROM and international sympathy towards its position throughout the years. This correlation indicates that the unmitigated optimism of the new Macedonian government about reaching a favourable compromise in 2018 through ‘behaving’ may not be entirely unwarranted.